An evaluation of the association between lockdown during the SARS-CoV-2 pandemic and prematurity at the Nice University Hospital - Lorenzi, Marine; Mayerus, Mathilde; Eleni Dit Trolli, Sergio; Hue-Bigé, Amandine; Legueult, Kévin; Guellec-Renne, Isabelle; François-Garret, Bérengère (Frontiers in Pediatrics, 2023)
Aim: To study the association between lockdown in France due to the SARS-CoV-2 pandemic and premature births at the Nice University Hospital. Methods: Data concerning neonates born at the level III maternity of the Nice University Hospital and immediately hospitalised in the neonatal reanimation unit or the neonatology department of the hospital with their mothers between the 1st of January 2017 and the 31st of December 2020, included. Results: We did not find a significant decrease in the global number of premature births < 37 weeks of gestation, in low weight at birth or a significant increase in stillbirths during lockdown compared to a period with no lockdown. The profiles of the mothers and their newborns were compared when birth occurred during lockdown versus no lockdown. Conclusion: We did not find any evidence of an association between lockdown and prematurity at the Nice University Hospital. This result is in agreement with meta-analyses published in the medical literature. The possible decrease in factors of risk of prematurity during lockdown is controversial.